Pengaruh Penggunaan Bahan Tambah Sebagai Substitusi Semen dan Agregat Terhadap Nilai Kuat Tarik Belah Beton Mutu Tinggi Hybrid - Ade Dwinta; Hilma Erliana; Chaira Chaira (Universitas Islam Raden Rahmat, Malang, 2024)
Concrete is a primary construction material, with aggregate as its main component. However, to meet the demands for more environmentally friendly and economical construction, alternative materials such as palm shell chunks (BCS), pozzolan sand, fly ash, and iron ore are needed. This study aims to evaluate the performance of concrete using variations of these aggregates and additional materials. The method employed includes testing the physical and mechanical properties, such as specific gravity, absorption, abrasion, and split tensile strength at 28 and 56 days. The results indicate that Split and BCS aggregates meet the abrasion standard of < 50%, with Split showing greater durability. The hybrid concrete (BMT-FBPP) using fly ash and pozzolan sand experienced a split tensile strength increase of 19.85% at 28 days and 24.57% at 56 days compared to normal concrete. It can be concluded that these alternative materials can enhance concrete performance, making them suitable for sustainable construction.